Ælred of Rievaulx's Pastoral Prayer and Its Basis in the Rule of Saint Benedict - Kardong, Terrence (Cistercian studies quarterly, 2010)
The article looks at the treatment of Saint Benedict about Alfred of Rievaulx's concept on abbatial images of the abbot as father and shepherd, and father of his people in his Holy Rule. It states that the monastic community is not a biological family, and the careless application of the concepts can do more harm than good to monastic existence. It mentions that the connection between the Rule of Saint Benedict and the Pastoral Prayer seems to be hard to make.